Core-shell structure adsorbent as well as preparation method and application thereof

By adopting core-shell structure design and ball forming technology in the adsorbent, combined with the addition of cellulose, the problem of poor adsorption performance of the adsorbent when removing impurities in naphtha is solved, and the adsorption performance, strength and wear resistance are achieved Improved performance, especially when dealing with various impurities in naphtha, has high selectivity.

CN119455923APending Publication Date: 2025-02-18CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411685187.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When existing adsorbents remove impurities in naphtha, their adsorption performance is poor, their strength and wear rate are low, making it difficult to effectively deal with complex components of molecules of different sizes.

Method used

Using ball forming technology, the first metal-loaded molecular sieve is used as the core and the second metal-loaded molecular sieve is a shell to form a core-shell structure adsorbent. The average pore size of the first molecular sieve is controlled to be smaller than the average pore size of the second molecular sieve, and to combine the addition of the first cellulose and the second cellulose, the adhesion and moldability of the material are improved.

Benefits of technology

It improves the adsorption performance, strength and wear resistance of adsorbents, and can effectively treat the removal of organic chlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds in naphtha, and has high selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005149251460000101
    Figure BDA0005149251460000101
  • Figure BDA0005149251460000111
    Figure BDA0005149251460000111
Patent Text Reader

Abstract

The invention provides a core-shell structure adsorbent as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing raw materials including a first molecular sieve, a first metal source and water, and carrying out a first reaction to obtain a first metal-loaded molecular sieve; mixing raw materials comprising a second molecular sieve, a second metal source and water, and then carrying out a second reaction to obtain a second metal-loaded molecular sieve; mixing raw materials including a first metal-loaded molecular sieve, a first binder and first cellulose to obtain a first mixture; mixing raw materials including a second metal-loaded molecular sieve, a second binder and second cellulose to obtain a second mixture; performing first rolling ball forming and second rolling ball forming on the first mixture and a first peptizing agent to obtain a core-shell structure precursor, and sequentially performing first standing, drying and roasting to obtain the core-shell structure adsorbent. The adsorbent has a relatively high removal rate on impurities in naphtha.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adsorbents, and in particular to a core-shell structure adsorbent and a preparation method and application thereof. Background Art

[0002] Naphtha is one of the main raw materials for producing high-octane gasoline and is also the main raw material in catalytic reforming process and steam cracking process for producing ethylene. If the organic chlorine content in it is too high, it will aggravate the corrosion of the equipment, which is not conducive to the long-term operation and safe production of the device, and the chlorine content in the obtained finished oil will also be too high; the nitrogen content and sulfur content in naphtha have a significant impact on the catalyst activity and life of the catalytic reforming unit, which can cause some catalysts to be poisoned and deactivated, reduce catalytic efficiency and increase production costs. The presence of oxygen-containing compounds is not conducive to the later deep processing of naphtha. Therefore, it is necessary to control the organic chlorine, nitrogen content, sulfur content and oxygen-containing compounds in naphtha to meet the index requirements.

[0003] Adsorbent is a solid substance that can effectively adsorb certain components from gas or liquid, with suitable pore structure and surface structure; has strong adsorption capacity for adsorbate; generally does not react chemically with adsorbate and medium; is easy to manufacture and regenerate; has excellent adsorption and mechanical properties. Molecular sieve adsorbent is a special adsorbent with a highly ordered crystal structure and a series of fixed-size pores inside. These pores can selectively adsorb and separate molecules of different sizes and shapes. The pore size can be adjusted as needed to meet the adsorption requirements of different molecules. Molecular sieves are widely used in petrochemical, gas separation, catalyst preparation and other fields.

[0004] The currently reported adsorbent for removing impurities from naphtha is a molecular sieve adsorbent. Therefore, molecular sieve adsorbents are selected to treat impurities in naphtha. Molecular sieve adsorbents are generally composed of molecular sieve raw powder and binder. Inorganic acids, such as hydrochloric acid, nitric acid and other peptizers, need to be added to play a bonding role. However, for rolling ball forming, such inorganic acid peptization is used. The material is relatively loose and it is difficult to achieve normal ball formation. Even if it is barely balled, its sphericity and strength are not ideal, and high wear will also shorten the service life of the adsorbent. Modifying molecular sieves with a single metal cannot simultaneously meet the effects of changing the pH, polarity, and activity of molecular sieves. Molecular sieves cannot handle complex components with different molecular diameters because their pore sizes are single. When the molecular diameter treated is larger than the molecular sieve pore diameter, it not only fails to achieve a good adsorption effect, but also blocks the molecular sieve pores, causing the adsorption performance of the molecular sieve to decrease, and coking is prone to occur on the surface and pores of the molecular sieve during the regeneration stage. Summary of the invention

[0005] The main purpose of the present invention is to provide a core-shell structure adsorbent and a preparation method and application thereof, so as to solve the problems of poor adsorption performance, low strength and low abrasion rate of the adsorbent in the prior art.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a core-shell structure adsorbent is provided, and the preparation method comprises the following steps: step S1, mixing raw materials including a first molecular sieve, a first metal source and water and then performing a first reaction to obtain a molecular sieve loaded with the first metal; step S2, mixing raw materials including a second molecular sieve, a second metal source and water and then performing a second reaction to obtain a molecular sieve loaded with the second metal; step S3, mixing raw materials including a molecular sieve loaded with the first metal, a first binder and a first cellulose to obtain a first mixture; step S4, mixing raw materials including a molecular sieve loaded with the second metal, a second binder and a second cellulose to obtain a second mixture; step S5, performing a first rolling ball molding on the first mixture and a first peptizing agent to obtain a core structure precursor; step S6, performing a second rolling ball molding on the core structure precursor in the second mixture and a second peptizing agent to obtain a core-shell structure precursor; step S7, performing a first standing, drying and calcining on the core-shell structure precursor in sequence to obtain a core-shell structure adsorbent; wherein the average pore size of the first molecular sieve is smaller than the average pore size of the second molecular sieve.

[0007] Furthermore, the average pore size of the first molecular sieve is 0.2nm-1.1nm; and / or the average pore size of the second molecular sieve is 0.25nm-1.2nm; preferably, the difference between the average pore size of the second molecular sieve and the average pore size of the first molecular sieve is 0.05nm-1nm.

[0008] Furthermore, in the above step S1, the mass ratio of the first molecular sieve to the first metal source is 1:0.006~0.04; and / or, the temperature of the first reaction is 80~110°C; and / or, the time of the first reaction is 1~4h; and / or, in step S2, the mass ratio of the second molecular sieve to the second metal source is 1:(0.006~0.04); and / or, the temperature of the second reaction is 80~110°C; and / or, the time of the second reaction is 1~4h.

[0009] Furthermore, the mass ratio of the first metal-loaded molecular sieve to the first binder is 5:5 to 7:3; and / or the mass content of the first cellulose in the first mixture is 0.5 to 5wt%; and / or the mass ratio of the second metal-loaded molecular sieve to the second binder is 5:5 to 7:3; and / or the mass content of the second cellulose in the second mixture is 0.5 to 5wt%.

[0010] Furthermore, in the above step S5, the mass ratio of the first mixture to the first peptizing agent is 1:(0.3-1.5); and / or, in step S6, the mass ratio of the first mixture, the second mixture and the second peptizing agent is 1:(0.5-2):(0.25-3).

[0011] Furthermore, in the above step S7, the first standing time is 12 to 36 hours; and / or the water content of the core-shell structure precursor after drying does not exceed 2wt%; and / or the calcination temperature is 400 to 600°C; and / or the calcination insulation time is 1 to 6 hours.

[0012] Furthermore, the average particle size of the above-mentioned core structure precursor is 0.8-1.2 mm; the preferred step S5 includes: step S51, subjecting the first mixture and the first peptizing agent to a third ball forming to obtain an intermediate product; step S52, crushing and second standing the intermediate product in sequence to obtain an intermediate powder; step S53, subjecting the intermediate powder to a fourth ball forming to obtain a core structure precursor; wherein the average particle size of the intermediate product is 1.2-2 mm; and / or the second standing time is 12-36 h.

[0013] Further, the first molecular sieve and the second molecular sieve are each independently selected from any one or more of 5A molecular sieve, 4A molecular sieve, 3A molecular sieve, 10X molecular sieve, 13X molecular sieve, NaY molecular sieve, LTA molecular sieve, ZSM-22 molecular sieve, SAPO-11 molecular sieve, SAPO-34 molecular sieve, SAPO-5 molecular sieve and ZSM-5 zeolite; and / or, the first metal source and the second metal source are each independently selected from any one or more of potassium nitrate, barium nitrate, lithium nitrate, strontium nitrate, manganese nitrate, calcium nitrate, cobalt nitrate, nickel nitrate, iron nitrate, cadmium nitrate, copper nitrate, silver nitrate, zinc nitrate, lanthanum nitrate and cerium nitrate, preferably, the metal types of the first metal source and the second metal source are different; and / or, The first binder and the second binder are each independently selected from any one or more of kaolin, halloysite, attapulgite, bentonite, and pseudo-boehmite, and preferably the first binder and the second binder are of different types; and / or the first cellulose and the second cellulose are each independently selected from any one or more of methyl cellulose, ethyl cellulose, carboxymethyl cellulose, and hydroxymethyl cellulose, and preferably the first cellulose and the second cellulose are each independently methyl cellulose; and / or the first peptizing agent and the second peptizing agent are each independently a mixture of nitric acid solution and oxalic acid solution; preferably, the mass concentration of the nitric acid solution is 0.5-5.0%, the mass concentration of the oxalic acid solution is 2-5%, and the volume ratio of the nitric acid solution to the oxalic acid solution is 1:(1-1.2).

[0014] According to another aspect of the present invention, a core-shell structure adsorbent is provided, which is prepared by the above-mentioned preparation method; preferably, the average particle size of the core-shell structure adsorbent is 2 to 2.5 mm; and / or the strength of the core-shell structure adsorbent is ≥ 40N / particle; and / or the specific surface area of ​​the core-shell structure adsorbent is 423 to 513 cm 2 / g; and / or, the abrasion rate of the core-shell structure adsorbent is 0.07-0.2%; and / or, the bulk density of the core-shell structure adsorbent is 673-720 kg / m 3 .

[0015] According to another aspect of the present invention, there is provided a use of the aforementioned core-shell structure adsorbent in the removal of impurities from naphtha.

[0016] Applying the technical solution of the present application, the present application adopts the rolling ball forming technology, with the first metal-loaded molecular sieve as the core, the second metal-loaded molecular sieve as the shell, and the average pore size of the first molecular sieve is controlled to be smaller than the average pore size of the second molecular sieve, to form a core-shell structure adsorbent. This structural design overcomes the influence of the pore size limitation of a single molecular sieve on the adsorption performance. Through the synergistic effect of the core-shell structure, the adsorbent can not only adsorb impurities with smaller molecular diameters, but also process complex components with larger molecular diameters, thereby helping to improve the adsorption effect and processing capacity of molecules of different sizes. In addition, the addition of the first cellulose and the second cellulose helps to improve the adhesion and formability of the material, and helps to improve the structural stability and strength of the adsorbent during the balling process. Therefore, the core-shell structure adsorbent prepared by the preparation method of the present application has excellent adsorption performance, strength and wear resistance, especially for the removal of organochlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds in naphtha has high selectivity. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0018] As analyzed in the background technology of this application, the adsorbent in the prior art has the problems of poor adsorption performance, low strength and low abrasion rate. In order to solve this problem, this application provides a core-shell structure adsorbent and its preparation method and application.

[0019] In a typical embodiment of the present application, a method for preparing a core-shell structure adsorbent is provided, and the preparation method comprises the following steps: step S1, mixing raw materials including a first molecular sieve, a first metal source and water, and then performing a first reaction to obtain a first metal-loaded molecular sieve; step S2, mixing raw materials including a second molecular sieve, a second metal source and water, and then performing a second reaction to obtain a second metal-loaded molecular sieve; step S3, mixing raw materials including a first metal-loaded molecular sieve, a first binder and a first cellulose to obtain a first mixture; step S4, mixing raw materials including a second metal-loaded molecular sieve, a second binder and a second cellulose to obtain a second mixture; step S5, performing a first ball forming on the first mixture and a first peptizing agent to obtain a core structure precursor; step S6, performing a second ball forming on the core structure precursor in the second mixture and a second peptizing agent to obtain a core-shell structure precursor; step S7, performing a first standing, drying and calcining on the core-shell structure precursor in sequence to obtain a core-shell structure adsorbent; wherein the average pore size of the first molecular sieve is smaller than the average pore size of the second molecular sieve.

[0020] The present application adopts rolling ball forming technology, with the first metal-loaded molecular sieve as the core, the second metal-loaded molecular sieve as the shell, and the average pore size of the first molecular sieve is controlled to be smaller than the average pore size of the second molecular sieve, forming a core-shell structure adsorbent. This structural design overcomes the influence of the pore size limitation of a single molecular sieve on the adsorption performance. Through the synergistic effect of the core-shell structure, the adsorbent can not only adsorb impurities with smaller molecular diameters, but also process complex components with larger molecular diameters, thereby helping to improve the adsorption effect and processing capacity of molecules of different sizes. In addition, the addition of the first cellulose and the second cellulose helps to improve the adhesion and formability of the material, and helps to improve the structural stability and strength of the adsorbent during the balling process. Therefore, the core-shell structure adsorbent prepared by the preparation method of the present application has excellent adsorption performance, strength and wear resistance, especially for the removal of organochlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds in naphtha has high selectivity.

[0021] In one embodiment of the present application, the average pore size of the first molecular sieve is 0.2nm~1.1nm; and / or, the average pore size of the second molecular sieve is 0.25nm~1.2nm; preferably, the difference between the average pore size of the second molecular sieve and the average pore size of the first molecular sieve is 0.05nm~1nm.

[0022] It is preferred to control the average pore size of the first molecular sieve and the average pore size of the second molecular sieve within the above range, which helps to improve the processing capacity and selective adsorption effect of the adsorbent for complex components. It is preferred to control the difference between the average pore size of the second molecular sieve and the average pore size of the first molecular sieve within the above range, which helps to improve the adsorption performance of the adsorbent while improving the structural stability of the adsorbent.

[0023] In one embodiment of the present application, in the above step S1, the mass ratio of the first molecular sieve to the first metal source is 1:(0.006~0.04); and / or the temperature of the first reaction is 80~110°C; and / or the time of the first reaction is 1~4h; and / or, in step S2, the mass ratio of the second molecular sieve to the second metal source is 1:(0.006~0.04); and / or the temperature of the second reaction is 80~110°C; and / or the time of the second reaction is 1~4h.

[0024] It is preferred to control the mass ratio of the first molecular sieve to the first metal source and the mass ratio of the second molecular sieve to the second metal source within the above range, which helps to provide an appropriate amount of metal active sites on the surface and in the pores of the molecular sieve, thereby helping to improve the activity and selectivity of the adsorbent. It is preferred to control the temperature and time of the first reaction and the temperature and time of the second reaction within the above range, which helps to improve the exchange efficiency between the metal ions and the molecular sieve, improve the uniformity of the distribution of the metal ions in the molecular sieve, thereby helping to improve the adsorption performance of the adsorbent, especially improving the selective removal ability of various impurities such as organic chlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds in naphtha.

[0025] In one embodiment of the present application, the mass ratio of the first metal-loaded molecular sieve to the first binder is 5:5 to 7:3; and / or, the mass content of the first cellulose in the first mixture is 0.5 to 5wt%; and / or, the mass ratio of the second metal-loaded molecular sieve to the second binder is 5:5 to 7:3; and / or, the mass content of the second cellulose in the second mixture is 0.5 to 5wt%.

[0026] It is preferred to control the mass ratio of the first metal-loaded molecular sieve to the first binder, and the mass ratio of the second metal-loaded molecular sieve to the second binder within the above range, which helps to make the molecular sieve and the binder have a good combination, neither sacrificing the adsorption capacity of the molecular sieve too much, nor causing molding difficulties due to insufficient binder, thereby helping to improve the strength and wear resistance of the adsorbent. It is preferred to control the mass content of the first cellulose in the first mixture and the mass content of the second cellulose in the second mixture within the above range, which helps to enhance the structural stability of the adsorbent and improve its adsorption efficiency. In addition, cellulose can form a microporous structure during drying and roasting, which helps to increase the specific surface area of ​​the adsorbent, improve the mass transfer performance of the adsorbent, and enable the adsorbent to more effectively capture and remove impurities in naphtha.

[0027] In one embodiment of the present application, in the above step S5, the mass ratio of the first mixture to the first peptizing agent is 1:(0.3-1.5); and / or, in step S6, the mass ratio of the first mixture, the second mixture and the second peptizing agent is 1:(0.5-2):(0.25-3).

[0028] Preferably, the mass ratio of the first mixture and the first peptizing agent, the mass ratio of the first mixture, the second mixture and the second peptizing agent are controlled within the above range, which helps to make the material have sufficient viscosity and fluidity during the ball rolling forming process, thereby helping to improve the strength and wear resistance of the adsorbent finally formed. The reasonable addition amount of the peptizing agent not only affects the forming of the adsorbent, but also affects its pore structure and surface properties, thereby affecting the adsorption performance. By optimizing the mass ratio of the peptizing agent, the pore size distribution of the adsorbent can be adjusted, which helps to improve its selective adsorption capacity for impurities of different molecular sizes in naphtha.

[0029] In one embodiment of the present application, in the above step S7, the first standing time is 12 to 36 hours; and / or the water content of the core-shell structure precursor after drying does not exceed 2wt%; and / or the calcination temperature is 400 to 600°C; and / or the calcination insulation time is 1 to 6 hours.

[0030] Preferably, the first standing time is controlled within the above range, which helps to make the distribution of water in the core-shell structure precursor more uniform, promotes the further combination of the molecular sieve and the binder, and thus helps to enhance the structural stability of the adsorbent. The adsorbent removes water slowly and evenly during the drying process, avoiding the internal stress concentration caused by direct roasting, resulting in structural damage, thereby helping to improve the mechanical strength of the adsorbent and reducing the possibility of breakage and wear of the adsorbent. Preferably, the roasting temperature and time are controlled within the above range, which helps to stabilize the metal active components and binder in the adsorbent, optimize the pore structure, help to increase the specific surface area of ​​the adsorbent, enhance the selective adsorption capacity of impurities of different molecular sizes, and avoid the problems of pore collapse and metal activity loss that may be caused by high temperature and long-term roasting.

[0031] In order to further improve the adsorption performance, strength and wear resistance of the adsorbent, in one embodiment of the present application, the average particle size of the above-mentioned core structure precursor is preferably 0.8-1.2 mm; the preferred step S5 includes: step S51, subjecting the first mixture and the first peptizing agent to a third rolling ball molding to obtain an intermediate product; step S52, crushing and second standing the intermediate product in sequence to obtain an intermediate powder; step S53, subjecting the intermediate powder to a fourth rolling ball molding to obtain a core structure precursor; wherein the average particle size of the intermediate product is 1.2-2 mm; and / or the second standing time is 12-36 h.

[0032] In one embodiment of the present application, the above-mentioned first ball forming, second ball forming, third ball forming and fourth ball forming are all carried out in a ball forming machine. Preferably, the diameter of the ball forming machine is 1 to 1.5 m, the horizontal inclination angle of the turntable is 10 to 70°, and the turntable speed is 10 to 80 r / min.

[0033] In one embodiment of the present application, the first molecular sieve and the second molecular sieve are each independently selected from 5A molecular sieve, 4A molecular sieve, 3A molecular sieve, 10X molecular sieve, 13X molecular sieve, NaY molecular sieve, LTA molecular sieve, ZSM-22 molecular sieve, MCM-41 molecular sieve, SAPO-11 molecular sieve, SAPO-34 molecular sieve, SAPO-5 molecular sieve and ZSM-5 zeolite. Any one or more; and / or, the first metal source and the second metal source are each independently selected from potassium nitrate, barium nitrate, lithium nitrate, strontium nitrate, manganese nitrate, calcium nitrate, cobalt nitrate, nickel nitrate, iron nitrate, cadmium nitrate, copper nitrate, silver nitrate, zinc nitrate, lanthanum nitrate, cerium nitrate. Any one or more; preferably, the metal species of the first metal source and the second metal source are The first binder and the second binder are of different types; and / or the first binder and the second binder are each independently selected from any one or more of kaolin, halloysite, attapulgite, bentonite, and pseudo-boehmite, and preferably the first binder and the second binder are of different types; and / or the first cellulose and the second cellulose are each independently selected from any one or more of methyl cellulose, ethyl cellulose, carboxymethyl cellulose, and hydroxymethyl cellulose, and preferably the first cellulose and the second cellulose are each independently methyl cellulose; and / or the first peptizing agent and the second peptizing agent are each independently a mixture of a nitric acid solution and an oxalic acid solution; preferably, the mass concentration of the nitric acid solution is 0.5-5.0%, the mass concentration of the oxalic acid solution is 2-5%, and the volume ratio of the nitric acid solution to the oxalic acid solution is 1:(1-1.2).

[0034] Preferably, the types of the first molecular sieve and the second molecular sieve are controlled within the above range, which helps to increase the specific surface area of ​​the core-shell structure adsorbent, thereby helping to improve the adsorption performance of the core-shell structure adsorbent. The different metal types of the first metal source and the second metal source help to give full play to the synergistic effect between different metals, thereby helping to improve the core-shell structure adsorbent for the selective removal of organic chlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds in naphtha. The different types of the first binder and the second binder help to further improve the strength and wear resistance of the core-shell structure adsorbent. In the specific implementation process, the first binder is preferably pseudo-boehmite and the second binder is kaolin. Preferably, the cellulose is methyl cellulose, which helps to build a more stable structure inside the adsorbent. At the same time, the addition of cellulose helps to improve the fluidity and molding properties of the material, thereby helping to improve the strength and wear resistance of the adsorbent. The first peptizing agent and the second peptizing agent are a mixture of a nitric acid solution and an oxalic acid solution of a specific concentration, and the volume ratio of the nitric acid solution to the oxalic acid solution is controlled within the above range, which helps to optimize the physical and chemical reactions during the peptization process, promote the bonding of the molecular sieve and the binder, and avoid the structural damage that may be caused by excessive acidification, thereby helping to improve the stability of the adsorbent.

[0035] In another typical embodiment of the present application, a core-shell structure adsorbent is provided. The core-shell structure adsorbent is prepared by the aforementioned preparation method.

[0036] Since the core-shell structure adsorbent is prepared by the preparation method of the present application, the core-shell structure adsorbent has excellent adsorption performance, strength and wear resistance, especially for the removal of organic chlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds in naphtha. It has high selectivity.

[0037] In one embodiment of the present application, the average particle size of the core-shell structure adsorbent is 2-2.5 mm; and / or the strength of the core-shell structure adsorbent is ≥40 N / particle; and / or the specific surface area of ​​the core-shell structure adsorbent is 423-513 cm 2 / g; and / or, the abrasion rate of the core-shell structure adsorbent is 0.07-0.2%; and / or, the bulk density of the core-shell structure adsorbent is 673-720 kg / m 3 .

[0038] The core-shell structure adsorbent having the above average particle size, strength, specific surface area, attrition rate and bulk density has better adsorption performance, especially for the adsorption of organic chlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds in naphtha, and has a longer service life.

[0039] In one embodiment of the present application, the core-shell structure adsorbent can be heated to remove the adsorbate, thereby achieving regeneration, and the heating temperature is 200-600°C.

[0040] In another typical embodiment of the present application, there is provided the use of the aforementioned core-shell structure adsorbent in the removal of impurities from naphtha.

[0041] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0042] Example 1

[0043] 1.5 kg of 5A molecular sieve was added into 9 kg of deionized water and fully dispersed, and stirred in a constant temperature water bath in a 90°C atmospheric pressure reactor. Then 15 g of copper nitrate was weighed, dissolved in 1 kg of deionized water, and added into the reactor for the first reaction at a constant temperature for 1.5 h. After washing and drying, Cu-5A molecular sieve modified with Cu was obtained. The average pore size of the 5A molecular sieve was 0.46 nm.

[0044] 1.5 kg of 13X molecular sieve was added into 9 kg of deionized water and fully dispersed, and stirred in a constant temperature water bath in a reactor at 90°C. Then 15 g of barium nitrate was weighed and dissolved in 1 kg of deionized water, and added into the reactor for a second reaction at a constant temperature for 1.5 h. After washing and drying, Ba-13X molecular sieve modified with Ba was obtained. The average pore size of the 13X molecular sieve was 0.95 nm.

[0045] Cu-5A molecular sieve and pseudo-boehmite were mixed in a dry basis weight ratio of 5.5:4.5, and 1 wt % of methyl cellulose was added and mixed evenly in a mixer for more than 30 minutes until the mixture was uniform, to obtain a first mixture.

[0046] Ba-13X molecular sieve and kaolin stone were mixed in a dry basis weight ratio of 5.5:4.5, and 1 wt % of methyl cellulose was added and mixed evenly in a mixer for more than 30 minutes until the mixture was uniformly mixed to obtain a second mixture.

[0047] Then, the first mixture is added to a ball rolling machine with a diameter of 1.5m, a horizontal inclination angle of the turntable of 45°, and a turntable speed of 50r / min. During the molding process, the first peptizing agent of nitric acid solution and oxalic acid solution is sprayed in small amounts and multiple times to form balls, and the mass concentration of the nitric acid solution is 0.5%, the mass concentration of the oxalic acid solution is 2%, the volume ratio of the nitric acid solution to the oxalic acid solution is 1:1, and the mass ratio of the first mixture to the first peptizing agent is 1:1. When the average diameter of the small balls of the first mixture in the ball rolling machine reaches 1.2mm, it is crushed into a coarse powder and left to age for 12h. The first coarse powder mixture after standing and aging is used as the core, and the first coarse powder mixture is added alternately in small amounts for rolling and balling. When the average diameter of the first mixture ball reaches 0.8 mm, the second mixture is added for rolling, and the second mixture and the second peptizer of nitric acid solution and oxalic acid solution are sprayed alternately in small amounts for multiple times to form balls, and the mass concentration of the nitric acid solution is 0.5%, the mass concentration of the oxalic acid solution is 2%, the volume ratio of the nitric acid solution to the oxalic acid solution is 1:1, and the mass ratio of the first mixture, the second mixture and the second peptizer is 1:1.2:2. After the ball diameter is qualified, the formed adsorbent wet ball is stood and aged for 12 hours. The aged wet ball is dried in a drying room until the moisture content of the semi-finished ball is as low as 2wt%, and the drying stage is considered to be over at this time.

[0048] The dried semi-finished balls were calcined in a muffle furnace, the calcination temperature in the muffle furnace was gradually increased, the final temperature was 550°C, and the final temperature was kept constant for 6 hours; the calcination was completed when the temperature cooled to room temperature. After calcination, the Cu-5A@Ba-13X core-shell structure adsorbent with an average particle size of 2.2 mm was obtained by sieving.

[0049] Example 2

[0050] The difference from Example 1 is that NaY molecular sieve is used to replace 5A molecular sieve, potassium nitrate is used to replace copper nitrate, and copper nitrate is used to replace barium nitrate, and finally a KY@Cu-13X core-shell structure adsorbent is obtained, and the average pore size of the NaY molecular sieve is 0.73 nm.

[0051] Example 3

[0052] The difference from Example 1 is that 10X molecular sieve is used to replace 13X molecular sieve, and zinc nitrate is used to replace barium nitrate, and finally a Cu-5A@Zn-10X core-shell structure adsorbent is obtained, and the average pore size of the 10X molecular sieve is 0.83 nm.

[0053] Example 4

[0054] The difference from Example 1 is that 10X molecular sieve is used to replace 5A molecular sieve, zinc nitrate is used to replace copper nitrate, and copper nitrate is used to replace barium nitrate, and finally a Zn-10X@Cu-13X core-shell structure adsorbent is obtained, and the average pore size of the 10X molecular sieve is 0.83 nm.

[0055] Example 5

[0056] The difference from Example 1 is that NaY molecular sieve is used to replace 13X molecular sieve, and potassium nitrate is used to replace barium nitrate, and finally a Cu-5A@KY core-shell structure adsorbent is obtained, and the average pore size of the NaY molecular sieve is 0.73 nm.

[0057] Example 6

[0058] The difference from Example 1 is that the mass of copper nitrate is 9 g, the mass ratio of 5A molecular sieve to copper nitrate is 1:0.006, the temperature of the first reaction is 80°C, the time of the first reaction is 1 h, the mass of barium nitrate is 9 g, the mass ratio of 13X molecular sieve to barium nitrate is 1:0.006, the temperature of the second reaction is 80°C, and the time of the second reaction is 1 h, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0059] Example 7

[0060] The difference from Example 1 is that the mass of copper nitrate is 60 g, the mass ratio of 5A molecular sieve to copper nitrate is 1:0.04, the temperature of the first reaction is 110°C, the time of the first reaction is 4 h, the mass of barium nitrate is 50 g, the mass ratio of 13X molecular sieve to barium nitrate is 1:0.04, the temperature of the second reaction is 110°C, and the time of the second reaction is 4 h, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0061] Example 8

[0062] The difference from Example 1 is that the mass of copper nitrate is 75 g, the mass ratio of 5A molecular sieve to copper nitrate is 1:0.05, the temperature of the first reaction is 120°C, the time of the first reaction is 0.5 h, the mass of barium nitrate is 75 g, the mass ratio of 13X molecular sieve to barium nitrate is 1:0.05, the temperature of the second reaction is 120°C, and the time of the second reaction is 0.5 h, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0063] Example 9

[0064] The difference from Example 1 is that the mass ratio of Cu-5A molecular sieve to pseudo-boehmite is 5:5, the mass content of methyl cellulose in the first mixture is 0.5wt%, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0065] Example 10

[0066] The difference from Example 1 is that the mass ratio of Cu-5A molecular sieve to pseudo-boehmite is 7:3, the mass content of methyl cellulose in the first mixture is 5wt%, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0067] Embodiment 11

[0068] The difference from Example 1 is that the mass ratio of Cu-5A molecular sieve to pseudo-boehmite is 7:2, the mass content of methyl cellulose in the first mixture is 6wt%, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0069] Example 12

[0070] The difference from Example 1 is that the mass ratio of Ba-13X molecular sieve to kaolin stone is 5:5, the mass content of methyl cellulose in the second mixture is 5wt%, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0071] Embodiment 13

[0072] The difference from Example 1 is that the mass ratio of Ba-13X molecular sieve to kaolin stone is 7:3, the mass content of methyl cellulose in the second mixture is 0.5wt%, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0073] Embodiment 14

[0074] The difference from Example 1 is that the mass ratio of Ba-13X molecular sieve to kaolin stone is 7:2, the mass content of methyl cellulose in the second mixture is 6wt%, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0075] Embodiment 15

[0076] The difference from Example 1 is that the mass ratio of the first mixture to the first peptizing agent is 1:1.5, and the mass ratio of the first mixture, the second mixture and the second peptizing agent is 1:2:0.25, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0077] Example 16

[0078] The difference from Example 1 is that the mass ratio of the first mixture to the first peptizing agent is 1:0.3, and the mass ratio of the first mixture, the second mixture and the second peptizing agent is 1:0.5:3, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0079] Embodiment 17

[0080] The difference from Example 1 is that the mass ratio of the first mixture to the first peptizing agent is 1:2, and the mass ratio of the first mixture, the second mixture and the second peptizing agent is 1:2.5:0.2, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0081] Embodiment 18

[0082] The difference from Example 1 is that hydroxymethyl cellulose is used to replace methyl cellulose, and finally a Cu-5A@Ba-13X core-shell structure adsorbent is obtained.

[0083] Comparative Example 1

[0084] The difference from Example 1 is that the first mixture and the second mixture are added into the ball rolling machine at the same time to finally obtain the adsorbent.

[0085] Comparative Example 2

[0086] The difference from Example 1 is that the second mixture is not added during the ball forming process, and the adsorbent is finally obtained.

[0087] Performance Testing

[0088] Compressive strength: tested on a particle compressive strength tester. 25 particles of each sample are randomly selected and tested using a spherical sample mode. The crushing force F / N is recorded and the average value is taken.

[0089] Abrasion rate: Tested according to standard GB / T10505.2-1989.

[0090] Bulk density: Determine according to the method specified in GB / T6286-2021 "Determination method of bulk density of molecular sieves".

[0091] Adsorption performance test: Impurities in naphtha include organic chlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds. The impurities in naphtha are removed by adsorption on a fixed bed using an adsorbent with an adsorbent-to-oil ratio of 0.8 and an air velocity of 0.8h -1 The adsorption process is that naphtha enters the adsorption tank from the bottom of the adsorption tank through the raw material delivery pump, and the naphtha after impurities are removed is transported from the top of the adsorption tank to the product tank through the raw material. The impurity content in the naphtha after impurities are removed is analyzed, and the impurity removal rate of the adsorbent is calculated. When the impurity removal rate of the adsorbent is lower than 90%, the adsorbent is regenerated at a heating temperature of 600°C. When the adsorbent is regenerated, but the impurity removal rate is still lower than 90%, the adsorbent is no longer used, and the service life of the adsorbent is calculated.

[0092] The adsorbents prepared in the examples and comparative examples were tested for specific surface area, compressive strength, abrasion rate, bulk density, impurity removal rate, and life of the adsorbent. The test results are shown in Table 1.

[0093] Table 1

[0094]

[0095]

[0096] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0097] The present application adopts rolling ball forming technology, with the first metal-loaded molecular sieve as the core, the second metal-loaded molecular sieve as the shell, and the average pore size of the first molecular sieve is controlled to be smaller than the average pore size of the second molecular sieve, forming a core-shell structure adsorbent. This structural design overcomes the influence of the pore size limitation of a single molecular sieve on the adsorption performance. Through the synergistic effect of the core-shell structure, the adsorbent can not only adsorb impurities with smaller molecular diameters, but also process complex components with larger molecular diameters, thereby helping to improve the adsorption effect and processing capacity of molecules of different sizes. In addition, the addition of the first cellulose and the second cellulose helps to improve the adhesion and formability of the material, and helps to improve the structural stability and strength of the adsorbent during the balling process. Therefore, the core-shell structure adsorbent prepared by the preparation method of the present application has excellent adsorption performance, strength and wear resistance, especially for the removal of organochlorine, organic nitrogen compounds, organic sulfur and oxygen-containing compounds in naphtha has high selectivity.

[0098] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a core-shell structure adsorbent, characterized in that: The preparation method comprises the following steps: Step S1, mixing raw materials including a first molecular sieve, a first metal source and water and performing a first reaction to obtain a first metal-loaded molecular sieve; Step S2, mixing raw materials including a second molecular sieve, a second metal source and water and performing a second reaction to obtain a second metal-loaded molecular sieve; Step S3, mixing the raw materials including the first metal-loaded molecular sieve, the first binder and the first cellulose to obtain a first mixture; Step S4, mixing the raw materials including the second metal-loaded molecular sieve, the second binder and the second cellulose to obtain a second mixture; Step S5, performing first ball forming on the first mixture and the first peptizing agent to obtain a core structure precursor; Step S6, subjecting the core structure precursor to second rolling ball forming in the second mixture and the second peptizing agent to obtain a core-shell structure precursor; Step S7, sequentially subjecting the core-shell structure precursor to first standing, drying and calcining to obtain the core-shell structure adsorbent; Wherein, the average pore size of the first molecular sieve is smaller than the average pore size of the second molecular sieve.

2. The preparation method according to claim 1, characterized in that: The average pore size of the first molecular sieve is 0.2nm-1.1nm; and / or the average pore size of the second molecular sieve is 0.25nm-1.2nm; preferably, the difference between the average pore size of the second molecular sieve and the average pore size of the first molecular sieve is 0.05nm-1nm.

3. The preparation method according to claim 1 or 2, characterized in that: In the step S1, the mass ratio of the first molecular sieve to the first metal source is 1:(0.006-0.04); and / or the temperature of the first reaction is 80-110° C.; and / or the time of the first reaction is 1-4 hours; And / or, in step S2, the mass ratio of the second molecular sieve to the second metal source is 1:0.006-0.04; and / or, the temperature of the second reaction is 80-110° C.; and / or, the time of the second reaction is 1-4 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that The mass ratio of the first metal-loaded molecular sieve to the first binder is 5:5 to 7:3; and / or the mass content of the first cellulose in the first mixture is 0.5 to 5 wt%; And / or, the mass ratio of the second metal-loaded molecular sieve to the second binder is 5:5 to 7:3; and / or, the mass content of the second cellulose in the second mixture is 0.5 to 5 wt%.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S5, the mass ratio of the first mixture to the first peptizing agent is 1:(0.3-1.5); And / or, in step S6, the mass ratio of the first mixture, the second mixture and the second peptizing agent is 1:(0.5-2):(0.25-3).

6. The preparation method according to any one of claims 1 to 5, characterized in that In the step S7, the first standing time is 12 to 36 hours; And / or, the water content of the core-shell structure precursor after drying is no more than 2wt%; And / or, the calcination temperature is 400-600° C.; and / or, the calcination insulation time is 1-6 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that The average particle size of the core structure precursor is 0.8-1.2 mm; preferably, step S5 comprises: Step S51, performing a third ball forming process on the first mixture and the first peptizing agent to obtain an intermediate product; Step S52, crushing the intermediate product and placing it aside for a second time in sequence to obtain an intermediate powder; Step S53, performing a fourth ball rolling forming on the intermediate powder to obtain the core structure precursor; Wherein, the average particle size of the intermediate product is 1.2 to 2 mm; and / or, the second standing time is 12 to 36 hours.

8. The preparation method according to any one of claims 1 to 7, characterized in that The first molecular sieve and the second molecular sieve are independently selected from any one or more of 5A molecular sieve, 4A molecular sieve, 3A molecular sieve, 10X molecular sieve, 13X molecular sieve, NaY molecular sieve, LTA molecular sieve, ZSM-22 molecular sieve, SAPO-11 molecular sieve, SAPO-34 molecular sieve, SAPO-5 molecular sieve and ZSM-5 zeolite; and / or, the first metal source and the second metal source are each independently selected from any one or more of potassium nitrate, barium nitrate, lithium nitrate, strontium nitrate, manganese nitrate, calcium nitrate, cobalt nitrate, nickel nitrate, iron nitrate, cadmium nitrate, copper nitrate, silver nitrate, zinc nitrate, lanthanum nitrate, and cerium nitrate, and preferably the first metal source and the second metal source have different metal types; and / or, the first binder and the second binder are independently selected from any one or more of kaolin, halloysite, attapulgite, bentonite, and pseudo-boehmite, and preferably the first binder and the second binder are of different types; and / or, the first cellulose and the second cellulose are each independently selected from any one or more of methyl cellulose, ethyl cellulose, carboxymethyl cellulose and hydroxymethyl cellulose, preferably the first cellulose and the second cellulose are each independently methyl cellulose; And / or, the first peptizing agent and the second peptizing agent are each independently a mixture of a nitric acid solution and an oxalic acid solution; preferably, the mass concentration of the nitric acid solution is 0.5-5.0%, the mass concentration of the oxalic acid solution is 2-5%, and the volume ratio of the nitric acid solution to the oxalic acid solution is 1:(1-1.2).

9. A core-shell structure adsorbent, characterized in that: The core-shell structure adsorbent is prepared by the preparation method described in any one of claims 1 to 8; preferably, the average particle size of the core-shell structure adsorbent is 2 to 2.5 mm; and / or the strength of the core-shell structure adsorbent is ≥ 40 N / particle; and / or the specific surface area of ​​the core-shell structure adsorbent is 423 to 513 cm 2 / g; and / or, the attrition rate of the core-shell structure adsorbent is 0.07-0.2%; and / or, the bulk density of the core-shell structure adsorbent is 673-720 kg / m 3 .

10. Use of the core-shell structure adsorbent according to claim 9 in removing impurities from naphtha.